ChAdOx1 and MVA based vaccine candidates against MERS-CoV elicit neutralising antibodies and cellular immune responses in mice. Issue 30 (27th June 2017) - Alharbi, Naif Khalaf; Padron-Regalado, Eriko; Thompson, Craig P.; Kupke, Alexandra; Wells, Daniel; Sloan, Megan A.; Grehan, Keith; Temperton, Nigel; Lambe, Teresa; Warimwe, George; Becker, Stephan; Hill, Adrian V.S.; et al.
Highlights: Inserting tPA leader sequence enhanced humoral responses of ChAdOx1 MERS. ChAdOx1 MERS elicited cellular immunity and neutralising antibodies. ChAdOx1 MERS responses were boosted by MVA MERS. Immunogenicity of a single dose of ChAdOx1 MERS was equivalent to 2 doses of MVA MERS. In MVA, F11 promoter enhanced cellular, but not humoral, immunogenicity, comparing to mH5 promoter. Abstract: The Middle East respiratory syndrome coronavirus (MERS-CoV) has infected more than 1900 humans, since 2012. The syndrome ranges from asymptomatic and mild cases to severe pneumonia and death. The virus is believed to be circulating in dromedary camels without notable symptoms since the 1980s. Therefore, dromedary camels are considered the only animal source of infection. Neither antiviral drugs nor vaccines are approved for veterinary or medical use despite active research on this area. Here, we developed four vaccine candidates against MERS-CoV based on ChAdOx1 and MVA viral vectors, two candidates per vector. All vaccines contained the full-length spike gene of MERS-CoV; ChAdOx1 MERS vaccines were produced with or without the leader sequence of the human tissue plasminogen activator gene (tPA) where MVA MERS vaccines were produced with tPA, but either the mH5 or F11 promoter driving expression of the spike gene. All vaccine candidates were evaluated in a mouse model in prime only or prime-boost regimens. ChAdOx1 MERS with tPA induced higher neutralising antibodies than ChAdOx1 MERS without tPA. A single dose of ChAdOx1 MERS with tPA elicited cellular immune responses as well as neutralising antibodies that were boosted to a significantly higher level by MVA MERS. The humoral immunogenicity of a single dose of ChAdOx1 MERS with tPA was equivalent to two doses of MVA MERS (also with tPA). MVA MERS with mH5 or F11 promoter induced similar antibody levels; however, F11 promoter enhanced the cellular immunogenicity of MVA MERS to significantly higher magnitudes. In conclusion, our study showed that MERS-CoV vaccine candidates could be optimized by utilising different viral vectors, various genetic designs of the vectors, or different regimens to increase immunogenicity. ChAdOx1 and MVA vectored vaccines have been safely evaluated in camels and humans and these MERS vaccine candidates should now be tested in camels and in clinical trials.